Predictive value of PaCO2 on mortality in patients with acute heart failure - Afifah, Yuri; Prasetya, Indra; Baskoro, Shalahuddin Suryo; Anjarwani, Setyasih (Universitas Brawijaya, 2025)
Background: Patients with AHF may experience fluctuations in carbon dioxide levels, resulting in either hypercapnia or hypocapnia. Recent research has highlighted the significance of the relationship between CO2 fluctuation and patient outcomes. Objective: The aim of this study was to explore the relationship between arterial carbon dioxide pressure (PaCO2) upon admission to the ICCU in patients with AHF. Methods: A single centre retrospective observational study was performed, the patient were enrolled from patient medical record between 2021 and 2023. Participants were divided into three groups based on PaCO2 levels. The study end point was length of hospitalization, mortality at ICCU and mortality in hospital. Statistical analysis used various tests to compare outcomes, with significance set at p<0.05, and ROC analysis evaluated mortality prediction. Result: The study included 150 patients: 97 with hypocapnia, 33 with normal PaCO2, and 19 with hypercapnia. In-hospital mortality was 37.5%, and 1-month mortality was 33.3% in the hypercapnia group. PaCO2 >45 mmHg was linked to higher in-hospital mortality (OR 6.900, p <0.001) and 30-day mortality (OR 5.600, p <0.001), PaCO2 <35 mmHg showing a protective association in ICCU and in-hospital mortality (OR 0.202, p<0.001) and 30-day mortality (OR 0.237, p<0.001). Length of stay was not significantly affected by either hypocapnia or hypercapnia. The ROC for predicting in-hospital mortality was 0.648 and for 30-day mortality was 0.626 in the PaCO2 >45 mmHg group. Conclusion: PaCO2 levels at ICCU admission predict mortality in AHF patients. Hypercapnia is associated with higher in-hospital and 30-day mortality, while hypocapnia appears protective.